Changes in triggering of ST-elevation myocardial infarction by particulate air pollution in Monroe County, New York over time: a case-crossover study - Meng Wang; Philip K. Hopke; Mauro Masiol; Sally W. Thurston; Scott Cameron; Frederick Ling; Edwin van Wijngaarden; Daniel Croft; Stefania Squizzato; Kelly Thevenet-Morrison; David Chalupa; David Q. Rich (BMC, 2019)
Abstract Background Previous studies have reported that fine particle (PM2.5) concentrations triggered ST elevation myocardial infarctions (STEMI). In Rochester, NY, multiple air quality policies and economic changes/influences from 2008 to 2013 led to decreased concentrations of PM2.5 and its major constituents (SO4 2−, NO3 −, elemental and primary organic carbon). This study examined whether the rate of STEMI associated with increased ambient gaseous and PM component concentrations was different AFTER these air quality policies and economic changes (2014-2016), compared to DURING (2008-2013) and BEFORE these polices and changes (2005-2007). Methods Using 921 STEMIs treated at the University of Rochester Medical Center (2005-2016) and a case-crossover design, we examined whether the rate of STEMI associated with increased PM2.5, ultrafine particles (UFP, < 100 nm), accumulation mode particles (AMP, 100-500 nm), black carbon, SO2, CO, and O3 concentrations in the previous 1-72 h was modified by the time period related to these pollutant source changes (BEFORE, DURING, AFTER). Results Each interquartile range (3702 particles/cm3) increase in UFP concentration in the previous 1 h was associated with a 12% (95% CI = 3%, 22%) increase in the rate of STEMI. The effect size was larger in the AFTER period (26%) than the DURING (5%) or BEFORE periods (9%). There were similar patterns for black carbon and SO2. Conclusions An increased rate of STEMI associated with UFP and other pollutant concentrations was higher in the AFTER period compared to the BEFORE and DURING periods. This may be due to changes in PM composition (e.g. higher secondary organic carbon and particle bound reactive oxygen species) following these air quality policies and economic changes.